2015
DOI: 10.4103/0019-509x.178404
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of medulloblastoma: 10 year experience of a referral institution in South India

Abstract: Early diagnosis and treatment is the key to management of medulloblastoma, which still needs to be achieved. Bulky tumors have a poor outcome, efforts should be aimed at complete surgery and giving risk stratification based treatment. Resources need to be allocated to make more conformal methods of radiotherapy available, which will decrease the growth abnormalities and cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Clinical characteristics were comparable with previous studies. [ 14 15 ] Nevertheless, the severity of disease, in our study, tended to be more aggressive. More than half of the patients had metastatic disease compared with previous studies.…”
Section: Discussioncontrasting
confidence: 43%
“…Clinical characteristics were comparable with previous studies. [ 14 15 ] Nevertheless, the severity of disease, in our study, tended to be more aggressive. More than half of the patients had metastatic disease compared with previous studies.…”
Section: Discussioncontrasting
confidence: 43%
“…Multipronged approach combining surgery, radiation and chemotherapy remains the cornerstone for the treatment of medulloblastoma, as these tumors gives an excellent response to radiation and chemotherapy subsequent to surgical resection. [ 16 ] However, the age, histology, tumor stage, and type of surgery are the major determinant of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…No studies attempted to formally analyze predictors of treatment abandonment in CNS tumors. However, authors of 12 studies reported possible causes of abandonment (Table ), based on their personal experience with patients, patient records, and knowledge of patients’ backgrounds . Only one (Chinese) study conducted a questionnaire with caregivers to identify reasons for abandonment .…”
Section: Overall Resultsmentioning
confidence: 99%